2013
DOI: 10.1016/j.neuropharm.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and anxiolytic potential of the multimodal antidepressant vortioxetine (Lu AA21004) assessed by behavioural and neurogenesis outcomes in mice

Abstract: Vortioxetine (Lu AA21004) is an investigational novel antidepressant with multimodal activity that functions as a 5-HT3, 5-HT7 and 5-HT(1D) receptor antagonist, 5-HT(1B) receptor partial agonist, 5-HT(1A) receptor agonist and inhibitor of the 5-HT transporter in vitro. Here we explore its anxiolytic and antidepressant potential in adult mice. Vortioxetine was assessed in BalB/cJ@RJ mice using the open-field and forced-swim tests (acute: p.o. 1 h, repeated: daily p.o. 21 days), and in 129S6/SvEvTac mice using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 58 publications
8
76
0
1
Order By: Relevance
“…Similarly, after chronic dosing, vortioxetine activates neuronal plasticity related genes, improves visual spatial memory deficits, and shows antidepressant-like activity in 12 months old mice, whereas fluoxetine has no effects on any of these measures in old mice [76]. Vortioxetine also increases cell proliferation in the hippocampal dentate gyrus faster than fluoxetine (3 days for vortioxetine compared to 10 days for fluoxetine) [77] in rats, and produces a larger degree of dendritic branching than fluoxetine after two weeks of dosing in mice [78].…”
Section: Vortioxetinementioning
confidence: 98%
“…Similarly, after chronic dosing, vortioxetine activates neuronal plasticity related genes, improves visual spatial memory deficits, and shows antidepressant-like activity in 12 months old mice, whereas fluoxetine has no effects on any of these measures in old mice [76]. Vortioxetine also increases cell proliferation in the hippocampal dentate gyrus faster than fluoxetine (3 days for vortioxetine compared to 10 days for fluoxetine) [77] in rats, and produces a larger degree of dendritic branching than fluoxetine after two weeks of dosing in mice [78].…”
Section: Vortioxetinementioning
confidence: 98%
“…Preclinical evidence showed that adult hippocampal neurogenesis may contribute to the mechanism of antidepressant drug action and BDNF is probably involved in this effect (Malberg et al, 2000;Guilloux et al, 2013;Sairanen et al, 2005). In fact BDNF has been implicated in regulating adult neurogenesis in the subgranular zone of the DG and is important for the regulation of the basal level of neurogenesis in adult mice (Lee et al, 2002;Waterhouse et al, 2012).…”
Section: Foxos Play a Inhibitory Role In Neurogenesis And Synaptogenesismentioning
confidence: 99%
“…Administration of antidepressants will produce an increase in the number of new-borne neurons within the hippocampus (Malberg et al, 2000;Guilloux et al, 2013;Sairanen et al, 2005). The observation that current antidepressant drugs promote adult hippocampal neurogenesis provides a much stronger evidence on this link (Mahar et al, 2014;Zunszain et al, 2013).…”
Section: Foxos Play a Inhibitory Role In Neurogenesis And Synaptogenesismentioning
confidence: 99%
“…One of the most reproducible findings in antidepressant research is that different classes of antidepressants including TCAs, MAOIs and SSRIs increase hippocampal cell proliferation and neurogenesis [83,139,[144][145][146] after chronic, but not acute, treatment consistent with the time course for their onset of therapeutic action. Similar positive effects have been reported using novel therapeutic strategies.…”
Section: Hippocampal Neurogenesismentioning
confidence: 92%
“…Putative fast-acting antidepressants, including 5-HT7 receptor antagonist SB-269970 [53] and 5-HT4 receptor agonists RS67333 and prucalopride [83,85] induced an enhancement of hippocampal neurogenesis in a time course concordant with their onset of action. Very recently, a preclinical study using the multimodal antidepressant vortioxetine showed that a 21-day treatment with this drug was able to increase cell proliferation and survival and to stimulate the maturation of immature granule cells in the SGZ of the DG of the hippocampus [146] while a preliminary study revealed that such DG cell proliferation increase occurred after one day of treatment only [148]. Taken together, these data indicate that up regulation of hippocampal neurogenesis may be a common dominator of the mechanism of action of antidepressants.…”
Section: Hippocampal Neurogenesismentioning
confidence: 99%